The Puerto Rico Cardiovascular Risk-Estimation Study (PRCaRES): An Exploratory Assessment of New Patients in Physicians’ Offices - Monsanto, Homero A.; Renta-Muñoz, Antonio; Dones, Wistremundo; Comulada, Angel; Cidre, Carlos; Orengo, Juan Carlos (Puerto Rico Health Sciences Journal, 2014)
Objective: To determine the risk of developing coronary heart disease (CHD) in a cross-sectional sample of Puerto Rico residents through an analysis of the 10-year Framingham risk score. Methods: An exploratory, retrospective, cross-sectional study of the medical records of patients 35 years or older who each visited the office of 1 of the 4 participating physicians on or after July 1, 2007. Results: Data for 453 patients were extracted from the medical records, but 96 cases were excluded because of incomplete data or the patients’ not fulfilling the inclusion criteria, thus yielding a total sample of 357 patients. The average patient age was 58 years old (±11.8); the majority (58%) was female. Eight of 10 patients were either overweight or obese. Eighty-five percent reported having at least 1 cardio metabolic condition. Of these, 72.3% self-reported having hypertension; 38.4%, dyslipidemia; and 37.8%, diabetes. Many patients were not at goal for blood pressure or for lipid and glucose parameters nor were these patients taking any medication for these conditions. Nearly one-third of the participants had a 10% or greater 10-year risk of developing CHD. Compared with women, men were 3.3 times more likely to have a 10-year CHD risk of 10% or greater and 4.2 times more likely to have a risk of 20% or greater. Conclusion: A substantial number of patients had risk factors for developing CHD and were not at goal for specific parameters. Larger scale epidemiological studies should be conducted to assess CHD risk in Puerto Rico so that public health initiatives to reduce this risk might be proposed.